Assessment of Non-cultured Autologous Epidermal Cell Grafting Resuspended in Hyaluronic Acid for Repigmenting Vitiligo and Piebaldism Lesions: A Randomized Clinical Trial - Antoine Bertolotti; Giovanni Leone; Alain Taïeb; Emilie Soriano; Michel Pascal; Hervé Maillard; Nanja van Geel (Medical Journals Sweden, 2021)
The aim of this study was to assess the efficacy of non-cultured autologous epidermal cell grafting resuspended in hyaluronic acid, performed using a ready-to-use kit, compared with hyaluronic acid alone (neutral comparator) for repigmenting vitiligo and piebaldism lesions at 6 months. Two identified paired lesions per patient were randomized to be treated by either device. Devices with a ready-to-use kit were prepared by separate health professionals, to maintain blinding. A skin biopsy was digested using trypsin, and cells resuspended in hyaluronic acid solution. Among 38 patients screened, 36 (94.7%) patients, corresponding to 72 lesions, were analysed. For difficult-to-treat lesions, defined as those located on the wrist, elbow, and hands (n = 30), no repigmentation ≥ 50% was observed. For all other locations (n = 42), the success rate was significantly higher (p = 0.021) in the ready-to-use kit group (47.6% vs 9.5%) at 6 months and was maintained until 12 months. In conclusion, a single application of non-cultured epidermal cellular grafting using a ready-to-use kit was efficient at 6 months and at 1-year follow-up.